Deferoxamine Inhibits Acute Lymphoblastic Leukemia Progression through Repression of ROS/HIF-1α, Wnt/β-Catenin, and p38MAPK/ERK Pathways. (21st February 2022) - You, Hongliang; Wang, Dao; Wei, Linlin; Chen, Jiao; Li, Huanhuan; Liu, Yufeng
Abstract : Acute lymphoblastic leukemia (ALL) is the most common type of childhood cancer, with a feature of easy to induce multidrug resistance and relapse. Abundant studies have proved that iron overload strengthens the growth and metastasis of tumor cells. Herein, we found that deferoxamine (DFO) effectively decreased the concentration of intracellular iron in ALL cells. DFO inhibited proliferation, induced apoptosis, and obstructed cell cycle of ALL cells, whereas DFO and dextriferron (Dex) used in combination significantly decreased the sensitivity of ALL cells to DFO. Reactive oxygen species (ROS) level was reduced in ALL cells treated with DFO, and the combination of DFO and Dex reversed the effects of DFO. In vivo, DFO inhibited mouse tumor growth. Besides, cyclinD1, β -catenin, c-Myc, hypoxia inducible factor 1 (HIF-1), p-p38MAPK, and p-ERK1/2 protein levels were significantly downregulated, and the levels of prolyl hydroxylase-2 (PHD-2) were upregulated after treated with DFO, whereas Dex treatment reversed those in vivo and in vitro . In conclusion, DFO inhibited the proliferation and ALL xenograft tumor growth, obstructed the cell cycle, and induced apoptosis of ALL cells, probably via inactivating the ROS/HIF-1 α, Wnt/ β -catenin, and p38MAPK/ERK signaling.